Socio-cultural Approach to Accelerate UN SDGs Achievement in West Klampis Village of Madura Island - Nur Fadjrih Asyik; Ikhsan Budi Riharjo; Triyonowati; Khuzaini; Prawita Yani; Fastha Aulia Pradhani (International Journal Of Community Service, 2026)
Nowadays socio-economic has new challenges. By recent global pandemic, poverty, and the migrant issues, United Nation (UN) established 17 set of indicators of the country’s well-being called Sustainable Development Goals (SDGs). These components need to be reached by 2030 set by the UN. Indonesia, through their government institution has set 18 village SDGs to accommodate this. West Klampis as a maritime village has environmental potential based on their demographic. However, considering their background, the villagers need to be assisted since many of fishery resources has limited contributions of their own well-being. Furthermore, their Village-Owned Enterprise called Badan Usaha Milik Desa (BUMDES) Permata Bahari has lack of proper accounting recording and reporting. These conditions will obstruct the achievement of village SDGs. To adreess this, the community service team of Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya by using the cultural and environmental approach, lead the mapping process of West Klampis fishery potential and assisted the preparation of BUMDES Permata Bahari financial report. The mapping itself describes all fishery commodities along with the components such as packaging and labelling. What makes it interesting is the head of the team deliver it by using Maduranese local language. By this cultural approach, the participants listened carefully and followed up comprehensively. While the financial report assisted to the secretary of the entity and being upgraded using Microsoft (MS) Excel. This template effectifely used for the upcoming period and finally fulfill the pilars of financial statement quality.